Heroine’s journey to love: Spatial rhetoric in romantic subplots in BioWare’s fantasy RPGs - Bednorz , Magdalena (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This article explores the potential of digital games to encode references encompassing specific cultural ideas of romantic love within their spatial structures, thus helping guide the player’s interpretation of romance as they interact with and move through those spaces. It undertakes an analysis of romantic subplots in BioWare’s fantasy role-playing games, specifically those which reappropriate the courtly love trope, and discusses elements of that remediation which rely heavily on spatial metaphors and structures, including the shared experience of heroic journey, the role of questing for the development of romance, and spatial positioning of lovers on the game map. Through its analysis, the article explores how digital games can employ spatial rhetoric while approaching topics of love, and how they are equipped to represent the materiality and spatiality of love and love narratives.